Improving the Business Production of Sumedang Tofu Through Equipment Provision and Business Assistance: Peningkatan Produksi Usaha Tahu Sumedang Melalui Penyediaan Peralatan dan Pendampingan Usaha - Fatira AK, Marlya; Suadi, S.; Safrida, Eli; Sebayang, Rihat; Nurlinda, N. (Mattawang: Jurnal Pengabdian Masyarakat, 2020)
This article about efforts to increase the production of Sumedang Tofu as the small and micro business through the Supply of Equipment and Business Assistance. These programs do to increase the production of Sumedang tofu according to market needs. These programs expected that business owners understand how to make simple financial statements understand about healthy and safe ways to dispose of business waste, able to see business opportunities from the management of business waste know for future business development, Provide brand signs to introduce business to the wider community. The method used in this community service program is collecting data/information about prospective partners through surveys and interviews. The information is analyzed descriptively, implemented, and carried out an evaluation of the community service program as a whole to see compliance with the output target. The results show that the customer order service is able to be produced with tofu grinding machines with a capacity of 50 kg/hour, limited production equipment can be overcome with the engine the problem of recording business financial statements has now been able to be separated and carried out in accordance with the material that was submitted during the training for recording simple financial statements. Abstrak Artikel ini membahas tentang upaya peningkatan produksi tahu sumedang sebagai Usaha Kecil dan Mikro (UKM) melalui penyediaan alat dan bantuan usaha. Program ini dilakukan untuk meningkatkan produksi tahu Sumedang sesuai kebutuhan pasar. Melalui program ini diharapkan para pelaku usaha memahami bagaimana membuat laporan keuangan yang sederhana, memahami tentang cara-cara yang sehat dan aman untuk membuang sampah usaha, mampu melihat peluang usaha dari pengelolaan sampah usaha tahu untuk pengembangan usaha kedepannya, Memberikan rambu merek untuk memperkenalkan usaha kepada masyarakat luas. Metode yang digunakan dalam program pengabdian masyarakat ini adalah pengumpulan data / informasi tentang calon mitra melalui survei dan wawancara. Informasi tersebut dianalisis secara deskriptif, dilaksanakan dan dilakukan evaluasi program pengabdian kepada masyarakat secara keseluruhan untuk melihat kesesuaian dengan target keluaran. Hasil penelitian menunjukkan bahwa customer order service mampu diproduksi dengan mesin gerinda tahu berkapasitas 50 kg/jam, terbatasnya alat produksi dapat diatasi dengan mesin permasalahan pencatatan laporan keuangan usaha kini sudah dapat dipisahkan dan dilaksanakan sesuai dengan materi yang disampaikan selama pelatihan pencatatan laporan keuangan sederhana.